Escaping the Build Trap (Audio Book) - Perri, Melissa (O'Reilly Media, Incorporated, 2019)
This audio book is for Product Managers of all levels (including the VP level) who understand that if companies want to remain innovative in today's market, they have to adopt a culture of learning and customer-centric practices that are focused on outcomes over outputs. This audio book provides Product Managers with a practical process and a toolbox of product management principles that can be applied to any company, big or small, and will help them produce real positive results. They will learn how to overcome product development roadblocks, the secrets to communicating and collaborating within a company structure, and how to build products that benefit both the business and the customer.